PENGAMANAN BARANG MILIK DAERAH DALAM MEWUJUDKAN AKUNTABILITAS PADA BADAN KEUANGAN KABUPATEN GORONTALO UTARA - Adam, Novita; Thalib, Maryati Kadir (JSAP : Journal Syariah and Accounting Public, 2022)
This study aims to analyze and describe how the implementation of securing Regional Property in realizing accountability in the North Gorontalo Regency Financial Board. the method used in this study is a qualitative approach by conducting interviews with employees in the accounting and asset sector. The results of the study show that the safeguarding of Regional Property in the North Gorontalo Regency Finance Agency has been effective but not yet accountable. The novelty of this study is what distinguishes it from previous research, namely the researcher includes elements of Regional Original Revenue (PAD) to assess accountability in securing Regional Property